Unilateral and bilateral training competitive archers differ in some potentially unhealthy neck-shoulder region movement behaviour characteristics - Mareike Schmitt; Lutz Vogt; Jan Wilke; Daniel Niederer (BMC Sports Science, Medicine and Rehabilitation, 2021)
Abstract Background Excessive unilateral joint loads may lead to overuse disorders. Bilateral training in archery is only performed as a supportive coordination training and as a variation of typical exercise. However, a series of studies demonstrated a crossover transfer of training-induced motor skills to the contralateral side, especially in case of mainly unilateral skills. We compared the cervical spine and shoulder kinematics of unilateral and bilateral training archers. Methods In this cross-sectional study, 25 (5 females, 48 ± 14 years) bilaterally training and 50 age-, sex- and level-matched (1:2; 47.3 ± 13.9 years) unilaterally training competitive archers were included. Cervical range of motion (RoM, all planes) and glenohumeral rotation were assessed with an ultrasound-based 3D motion analysis system. Upward rotation of the scapula during abduction and elevation of the arm were measured by means of a digital inclinometer and active shoulder mobility by means of an electronic caliper. All outcomes were compared between groups (unilaterally vs. bilaterally) and sides (pull-hand- vs. bow-hand-side). Results Unilateral and bilateral archers showed no between group and no side-to-side-differences in either of the movement direction of the cervical spine. The unilateral archers had higher pull-arm-side total glenohumeral rotation than the bilateral archers (mean, 95% CI), (148°, 144–152° vs. 140°, 135°-145°). In particular, internal rotation (61°, 58–65° vs. 56°, 51–61°) and more upward rotation of the scapula at 45 degrees (12°, 11–14° vs. 8°, 6–10°), 90 degrees (34°, 31–36° vs. 28°, 24–32°), 135 degrees (56°, 53–59° vs. 49°, 46–53°), and maximal (68°, 65–70° vs. 62°, 59–65°) arm abduction differed. The bow- and pull-arm of the unilateral, but not of the bilateral archers, differed in the active mobility of the shoulder (22 cm, 20–24 cm vs. 18 cm, 16–20 cm). Conclusions Unilaterally training archers display no unphysiologic movement behaviour of the cervical spine, but show distinct shoulder asymmetris in the bow- and pull-arm-side when compared to bilateral archers in glenohumeral rotation, scapula rotation during arm abduction, and active mobility of the shoulder. These asymmetries in may exceed physiological performance-enhancing degrees. Bilateral training may seems appropriate in archery to prevent asymmetries.